Maternal galactooligosaccharides supplementation programmed immune defense, microbial colonization and intestinal development in piglets. Issue 16 (24th June 2021) - Wu, Yujun; Zhang, Xiangyu; Pi, Yu; Han, Dandan; Feng, Cuiping; Zhao, Junying; Chen, Lijun; Che, Dongsheng; Bao, Hongxing; Xie, Zhengjun; Wang, Junjun
Abstract : Dietary GOS in sows nutritionally programmed intestinal Alloprevotella and plasma IgA in their offspring, contributing to a better intestinal barrier and growth performance of piglets. Abstract : The benefits of galactooligosaccharides (GOS) in neonates have been confirmed. However, the effects of nutritional programming by maternal GOS intervention on microbial colonization and intestinal development in the offspring remain unclear. In the present study, late gestational sows were fed with GOS (10 g d −1 added into the diet) or not until parturition, and the performances, immune status, microbiota composition and intestinal barriers in their piglets on day 21 were compared. GOS supplementation in pregnant sows improved their litter characteristics and the growth performance of their piglets during the neonatal stage (day 21), and elevated the plasma IgA levels in both sows and their piglets ( P < 0.05). GOS intervention enriched fecal Alloprevotella and Ruminoclostridium_1 in gestational sows and vertically increased fecal Alloprevotella and Ruminococcaceae in their piglets ( P < 0.05). Moreover, maternal GOS intervention increased fecal acetate ( P < 0.05) and improved the intestinal barriers of their piglets by upregulating intestinal tight junctions ( Occludin, Claudin-1, ZO-1 ), the goblet cell number and Mucin-2 ( P < 0.05), which correlated positively with the colonized microbiota ( P < 0.05). In summary, GOS supplementation for sows during late gestation nutritionally programmed maternal specific microbes and IgA of their offspring. This neonatal programming showed positive potential in promoting the intestinal barriers, immune defense, and growth performance of the piglets. Our findings provide evidence for maternal nutritional programming in neonates and insights for future application of GOS in maternal–neonatal nutrition.